Proses Asuhan Gizi Terstandar pada Pasien Acute Kidney Injury dengan Anemia Gravis - Ilmiati, Fadhilah; Pangestuti, Meitriana; Yuliastuti, Mariana (Jurnal Ilmiah Gizi dan Kesehatan (JIGK), 2025)
Acute Kidney Injury (AKI) is an acute renal disorder associated with serious complications, including anemia gravis and malnutrition, leading to increased mortality rate. Comprehensive management, including appropriate nutritional therapy, are crucial to prevent clinical deterioration in AKI patient with complication. This case study aims to demonstrate the implementation of a nutrition care process (NCP) to improve nutritional status and support medical treatment. Conducted in February 2025 on patient at dr. Soedirman Hospital, Kebumen, the study involved assessment including anthropometric measurements, biochemical analysis, clinical examination, and dietary intake evaluation. Nutrition diagnoses identified inadequate oral intake, decreased protein needs, and food-and nutrition- related knowledge deficit. The patient received a low protein low purine diet (1.725,71 kcal and 39,45 grams protein) along with nutritional education. The intervention achieved oral intake improvement (>80% adequacy, increased hemoglobin levels, and clinical symptom improvement (appetite, weakness, and paresthesia). All monitoring and evaluation parameters confirmed the intervention met its target.